(untitled) (CIPEEX, 2025)
The present study deals with rural leasing, governed by Decree No. 59,566/66, which classifies it as an agrarian contract. In this sense, an individual transfers rural property to another for purposes such as agriculture, extraction, or livestock management, among others. Despite the inherent risks, the rural lease contract stipulates that payment will be made in accordance with the terms of the contract, thus categorizing it as a standard rental agreement. This research seeks to carry out a study regarding Agrarian Law and the rural lease contract. The objective of the study is to analyze the main challenges encountered between tenants and lessors, such as environmental concerns and climate change, and explore paths towards more effective practices in rural leasing. Furthermore, the real need for this information collection for researchers in the area is analyzed. The research proposes the following problem: How are the advantages of rural leasing shared between tenants and lessors? And what are accesses to credit for investment like? Based on bibliographical research, seeking to observe, describe, analyze and collect data, using the inductive method, through documentary analysis of Law No. 4,504, of November 30, 1964, which provides for the Land Statute. In this sense, scientific work follows a path towards a grounded and coherent legal construction.